Dampak Perkembangan Teknologi Informasi dan Komunikasi Terhadap Perilaku Moral Remaja di SMA Negeri 3 Kota Kupang - Yana F. Taopan; Mintje Ratoe Oedjoe; Andy Nabu Sogen (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2019)
The aim of this research was to analyze the effect of using Mobile Phone and Internet concerning to the students morality, great efforts of family (parents), teachers (school) and society to protect students from the bad effects of mobile phone use and ideal solution towards the students morality, particularly students at SMA N 3 Kota Kupang. This research used a qualitative description method. Data of this research were gathered from 10 students who usually used mobile phone at class, counseling teachers, citizenship teachers, members of school extracurricular organization, students’ parents, religious scholars and society figures by interview, observation, and documentation technique. The result of this research showed that using mobile phone and internet have positive and negative effects towards the students morality. The positive effects of mobile phone could be used effectively and efficiently as the tool of communication, particularly when communicating  to others in a long distance. Further we could make online communication which allowed us to get any information on communication and information technology.